Sialylated IgG-Fc: a novel biomarker of chronic inflammatory demyelinating polyneuropathy. Issue 3 (26th March 2015) - Wong, Anna Hiu Yi; Fukami, Yuki; Sudo, Makoto; Kokubun, Norito; Hamada, Shinsuke; Yuki, Nobuhiro
Abstract : Objective: Sialylation in Fc portion of IgG plays a crucial role in the pathogenesis of autoimmune diseases and the working mechanism of intravenous immunoglobulin (IVIG). We aim to test whether IgG-Fc sialylation is a biomarker of disease activity for chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: By using specific lectins for sialylation, galactosylation and agalactosylation, lectin-enzyme assay and lectin blotting with pretreatment of IgG degradating enzyme of Streptococcus pyogenes were performed to compare the glycosylation levels of serum IgG-Fc (1) between patients of untreated CIDP (n=107) and normal control subjects (n=27), (2) among patients with untreated CIDP of different clinical severities and (3) before and after IVIG treatment of patients with CIDP (n=12). Results: Sialylation and galactosylation of IgG-Fc were significantly reduced in patients with CIDP than normal control subjects (p=0.003 and 0.033, respectively), whereas agalactosylation was increased in CIDP (p=0.21). Ratios of sialylated/agalactosylated IgG-Fc levels were significantly reduced in CIDP (p<0.001) and inversely related to disease severity (p=0.044). After IVIG treatment, levels of sialylated IgG-Fc significantly increased (p=0.003). Conclusions: Sialylation of IgG-Fc is reduced in CIDP. Its level correlated with clinical severity and increased after IVIG treatment. Sialylated as well as ratio of sialylated/agalactosylated IgG-Fc could be new measures to monitor the disease severity and treatment status in CIDP.